Efficient Erasure Reconstruction from Noisy Measurements - Scholze, Sam; Holmes, Austin; Gonzales, Tyler (My University, 2018)
The goal of this project is to efficiently reconstruct signals when some of the frame measurements are erased or subject to additive noise.
Color poster with text, graphs, and images.
Keywords: Posters; Mathematics; Parseval frames; Digital signals; Frames (linear algebra)